1981
DOI: 10.1103/physrevb.23.1339
|View full text |Cite
|
Sign up to set email alerts
|

Electron-spin-lattice relaxation in a one-dimensional system

Abstract: We have measured by the modulation technique at the X band the spin-lattice relaxation rate in the one-dimensional (CH3)4NMnC13, in the temperature range 20 -300 K. The experimental data are well described by the Bloembergen and Wang model. Below 4S K, an exchange-lattice relaxation process has been evidenced.The spin dynamics in one-dimensional (1D) materials has been extensively studied by magnetic resonance" and neutron diffusion techniques. ' In these materials, the exchange-narrowed electron-spin resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…1). At temperatures below 50 K, (T~)zE begins to increase due to the approach to the antiferromagnetic order resulting in a slowing down of the decrease of Tlk It is noted that a similar relaxation behaviour was observed in TMMC by Bourdel et al [22].…”
Section: Glass Sample Doped With 3 Wt% Fe203 (X = 003)supporting
confidence: 65%
See 1 more Smart Citation
“…1). At temperatures below 50 K, (T~)zE begins to increase due to the approach to the antiferromagnetic order resulting in a slowing down of the decrease of Tlk It is noted that a similar relaxation behaviour was observed in TMMC by Bourdel et al [22].…”
Section: Glass Sample Doped With 3 Wt% Fe203 (X = 003)supporting
confidence: 65%
“…Thus, the observed dependence is most likely due to the combined effect of the mechanisms involving TLS and cross relaxation. iii) In the most concentrated glass sample (3 wt.% Fe203) , exchange interaction is dominant; the relaxation is well described by the Bloembergen and Wang three-reservoir model [19][20][21][22]. Accordingly, Ti 1 is almost constant between 75 and 200 K, while it decreases rapidly with decreasing temperature below 75 K.…”
Section: Discussionmentioning
confidence: 92%
“…These values were higher than those measured from the sound velocity, which indicated that the Debye model was not adequate to describe the lattice in these salts. (41,42,43) TMMC and CHAC samples are ID systems very close to the ideal ISING model. A strong exchange interaction is present in them, the coupling being antiferromagnetic in the former while it is ferromagnetic in the latter.…”
Section: Magnetic Field Dependence Of Spin-lattice Relaxation In Thrementioning
confidence: 88%
“…The observed dependence for T < 80 K cannot be attributed to the Zeeman-exchange relaxafion, but it can be due to the exchange-lattice relaxation, because the coupling between exchange and lattice reservoirs diminishes at low temperature. The Zeeman-exchange relaxation becomes the most efficient process and we have an exchange bottleneck [16]. …”
Section: Study Of 2c4mnbrmentioning
confidence: 99%